La traduction de l’emprunt : coup de théâtre ou coup de grâce ? - Corinne Wecksteen (Lexis: Journal in English Lexicology)
This article deals with French loan words in English, with a particular emphasis on the specific problems they pose to translation and the various factors that may hinder the translation process. The study is based on a corpus of about fifteen examples, taken from 19th and 20th century British and American fiction. A brief presentation of the motivation of loan words shows how they are connected to the problem of connotation. This is followed by a study of the markers of French loan words in an English text, whether they appear in typographical, graphical or phonetic forms which may even infringe the laws of French grammar. Various shifts are then examined, whether there is restriction or extension of meaning, or even a connotative shift. Finally, the focus is on the strategies translators resort to when they have to translate into French an English text containing French loan words and the various problems raised in the process (calques and loss of the connotative value of French loan words).